Analysis and application of backfill mining in thin coal seams for preventing building damage - Bai, Erhu; Guo, Wenbing; Guo, Miningjie; Lou, Gaozhong; Tan, Yi (Penerbit Universiti Kebangsaan Malaysia, 2019)
As coal resources trapped under surface buildings impede the efficient mining of coal seams and constrain the sustainable development of coal mines, a super-high-water backfill mining technique for preventing building damage was adopted. According to the established model of equivalent mining height (EMH), the influence factors were obtained. Afterwards, a measurement to improve the backfill rate was analyzed based on the slurry fluidity. Meanwhile, the relationships between the backfill body compression and its influence factors were studied by numerical simulation. In this way, a more accurate EMH was obtained. To prove this trial practicable, the obtained EMH and the probability integral method were used to predict the surface movement and deformation of the C7401 panel. At the same time, a surface movement observation was set up to observe the mining influence on the surface ground and buildings. The comparison between the predicted and measured data indicated that they corresponded well with each other, the surface movement and deformation values were all controlled within grade I, which protected the surface buildings. Moreover, by applying the super-high-water backfill mining technique, not only building damage has been controlled within Grade I, but the impact on the ecological environment has been reduced also, such as surface subsidence, groundwater leakage and groundwater lowering, which is in harmony with the construction of green mines. The practical trial can provide a reference for mining under similar conditions and is vital for the sustainable development of the mining industry and economic growth.